Bioethanol Production from Corn Cob Trough Utilization of Agrobiomass Waste in East Java as Renewable Energy : a Review - Grezdipa Pratama, Harsya; Sari Kusuma Wijayanti, Widya; Devi Larasati, Annisa; Rekyan Permatasari, Olivia (Universitas Negeri Semarang, 2024)
The demand for energy from fossil fuels continues to surge along with the rapid development of industry and the economy. Efforts to reduce dependence on fossil energy, especially the limited petroleum, are crucial. Therefore, it is necessary to increase the utilization of other energy sources, especially bioethanol, which is renewable and environmentally friendly. The production of bioethanol is intensifying due to market stability, low costs, sustainability, its role as an alternative fuel, and the risk of fossil fuel depletion. Corn cob waste comprises various organic compounds, including 40-60% cellulose, 20-30% hemicellulose, and 15-30% lignin. These compounds can be transformed into various forms of bioenergy, including bioethanol, biogas, and bio-oil. The process of producing bioethanol from corn cobs involves pretreatment, hydrolysis, fermentation, and distillation. The production of bioethanol from corn cob waste consists of several stages: pretreatment, hydrolysis, fermentation, and distillation. Lignin impedes acid penetration before hydrolysis and inhibits microbial growth during fermentation, so it must be removed through alkaline pretreatment. Glucose production from alkali-treated corn cobs can be achieved through hydrolysis using chemical or enzymatic catalysts. Acid hydrolysis with 21% H2SO4 and 21% HCl is preferred due to its shorter operating time. On the other hand, the high cost of enzymes and the extended operating time diminish production efficiency. The acid hydrolysis method using 21% H2SO4 requires 1 hour, 2 hours, and 3 hours and uses 21% HCl at a temperature of 100°C with a yield of less than 10%. The production of bioethanol from corn cobs is carried out using the SHF and SSF methods. The SSF method yields a range of 1.94%-88.37%. The SHF method yields a range of 0.28%-0.57%. Distillation is employed to remove impurities from liquids contaminated by dissolved substances from corn cobs, which have varying boiling points. Vacuum distillation can achieve a purity level of 89%. Converting corn cob into bioethanol aids in reducing environmental pollution and promotes the use of clean energy.